Initial clinical experience with the GORE® CARDIOFORM ASD occluder for transcatheter atrial septal defect closure. Issue 3 (27th January 2017) - de Hemptinne, Quentin; Horlick, Eric M.; Osten, Mark D.; Millán, Xavier; Tadros, Victor‐Xavier; Pighi, Michele; Gonzalez Barlatey, Francisco; Alnasser, Sami M.; Miró, Joaquim; Asgar, Anita W.; Ibrahim, Réda
Abstract : Objectives: To report the initial clinical experience with a novel atrial septal defect (ASD) closure device, the GORE ® CARDIOFORM ASD Occluder (GCO). Background: Transcatheter closure has become the treatment of choice for secundum ASD. A wide range of occluder devices are available, but concern has been raised about the risk of cardiac erosion associated with rigid devices and future access to the left atrium Methods: Retrospective chart review of patients treated with the GCO at three Canadian centers. Primary outcomes were procedural success and residual shunting at follow‐up, as well as 30‐day major adverse events. Secondary outcomes included new onset atrial arrhythmias, wire frame fractures (WFF), and all cause mortality. Clinical, echocardiographic, procedural data, and follow‐up outcome variables were collected in each participating hospital. Results: Between February and December 2015, 26 patients (5 children and 21 adults) underwent transcatheter ASD closure with the GCO and were included in the study cohort. Procedural success was achieved in 22 of 26 patients (85%) and no major procedural complications were observed. Two patients (8%) presented new onset atrial tachyarrhythmia during early follow‐up (0–30 days). Follow‐up echocardiography (median of 119 days [IQR: 92–146]) demonstrated no residual shunt in all implanted patients. After a median clinical follow‐up of 174 days (IQR: 135–239), one patient died of an unrelated cause, there were no documented major adverse cardiovascular events. Fluoroscopic imaging of the device was performed in 20 patients (91%), and WFF was noted in five cases. No clinical consequence or device dysfunction was observed in these patients. Conclusions: In this first‐in‐man multicenter study, the GCO was safe and effective for ASD closure, with no major adverse events or residual shunt at follow‐up. © 2017 Wiley Periodicals, Inc.